Electronic and Magnetic Properties of K2Mn3S4 - Acharya, G. B.; Ghimire, M. P. (Journal of Nepal Physical Society, 2022)
Many opto-electronic and energy efficient devices depend on semiconductors’ direct as well as indirect band gap. Using spin-polarized density functional theory approach, we calculate the electronic structure and magnetic properties of K2Mn3S4. We found that this system has a ferrimagnetic ground state with a saturated magnetic moment of 10μB per unit cell. This was mostly caused by the antiferromagnetic interaction between the Mn (I) and Mn (II) atoms, with individual magnetic moment of 4.2 μB and 4.1 μB, respectively. More significantly, from the density of states and band structure calculations, K2Mn3S4 is noted as a semiconductor with an indirect band gap of 1.1 eV between the top of the valence band of spin up channel and bottom of the conduction bands of spin down channel, indicating the material as a promising candidate for photovoltaic and opto-electronic devices.